Pakistan : Sixth and Seventh Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
Monetary developments in the first half of 2003 were largely in line with expectations, except for credit to the private sector, which has accelerated significantly in recent months. The overall deficit of the consolidated government was 4.5 percent of GDP in 2002-03, lower than the program ceiling, and the Central Board of Revenue (CBR) collection exceeded the target by a small margin. Pakistan's macroeconomic performance has strengthened substantially over the past few years, with the 2002-03 outcome largely exceeding the Poverty Reduction and Growth Facility (PRGF) targets.